A Transdisciplinary Approach to Character Development: Islamic Teachings and Pancasila Values in Shaping Global and Faithful Students - Adiyono Adiyono; Sri Nurhayati; Mohammad Shahidul Islam; Habib Al-Badawi; Zohaib Hassan Sain; Hasan Abdul Wafi; K.J Vargheese (Universitas Muhammadiyah Surakarta, 2025)
Islam as a religion covers various aspects of human life, but research on Islam is often limited to theological or historical perspectives. This research aims to develop a methodological framework that integrates multidisciplinary, interdisciplinary, and transdisciplinary approaches to understand Islam as a comprehensive way of life in the context of the Pancasila Student Profile Strengthening Project (P5). P5 aims to develop the character of students who are faithful and devoted to God Almighty, have a global outlook, cooperate, be self-reliant, and think critically, and creatively. To achieve this goal, a Systematic Literature Review (SLR) was conducted using methodologies and tools that support systematic thinking, identification, feasibility testing, and meta-analysis through journal articles, books, research reports, and other sources published in the last 10 years. Literature Selection and Quality Assessment consists of Inclusion Literature that discusses about Multidisciplinary approaches are used to combine perspectives from sociology, anthropology, psychology, and economics. The interdisciplinary approach integrates theories and methods from different disciplines to create a deeper understanding of how Islamic teachings can support the character development of Pancasila learners. The transdisciplinary approach involves collaboration between academics and practitioners from different fields to produce practical solutions based on academic research from Google Scholar, Semantic Scholar, Eric, Crossref, and Science Direct databases. The research findings show that Islamic teachings influence public policy and governance, and interact with local culture in daily religious practices. The integration of Islamic teachings with Pancasila values can teach students about the importance of social justice, collective responsibility, and mental health.